Analisis kinerja kincir air savonius poros vertikal dengan dua sudu pada beberapa variasi debit - Duma, G.A.; Sule, L.; Hafid, H.D. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2023)
The Savonius waterwheel is a type of waterwheel with a vertical shaft rotation direction that can be used to convert the potential energy of water into energy of motion. This waterwheel works due to the difference in the force received at each blade. This test uses two semi-circular gutter blades which are paired oppositely to resemble the letter "S". The discharge variations given are opening valve 1 (damped 2), opening valve 2 (damped 1), and opening valve 3 (undamped). The results obtained show that opening valve 1 has the highest efficiency value of 18.97% with water power of 7.672 W and waterwheel power of 1.455 W.